2012
DOI: 10.1016/j.breast.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Local breast cancer recurrence after mastectomy and immediate breast reconstruction for invasive cancer: A meta-analysis

Abstract: This meta-analysis demonstrated no evidence for increased frequency of local breast cancer recurrence with IBR compared with mastectomy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 33 publications
2
53
0
4
Order By: Relevance
“…In contrast to mastectomy, IBR has been shown to provide better cosmetic outcome and superior quality of life, without compromising oncological safety (2)(3)(4)(5)(6)(7)(9)(10)(11)(12)(13)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to mastectomy, IBR has been shown to provide better cosmetic outcome and superior quality of life, without compromising oncological safety (2)(3)(4)(5)(6)(7)(9)(10)(11)(12)(13)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Al-Ghazal et al showed that patients who underwent IBR showed less psychological distress than patients who underwent delayed breast reconstruction (8). Furthermore, studies have shown that IBR is oncologically safe as local recurrence incidence following IBR is comparable to that after mastectomy (5,(9)(10)(11)(12)(13)(14). This led to increasing IBR in the United (16).…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy was not given to any patients (57). Furthermore, a meta-analysis by Gieni et al (34) found no differences in terms of the risk of recurrence between patients who underwent immediate reconstruction and those who underwent mastectomy alone. Guidelines regarding this issue generally indicate that immediate reconstruction is as safe oncologically as delayed reconstruction and offers patients an improved psychological profile (23)(24)(25)(26)(27).…”
Section: What Is the Appropriate Timing Of Breast Reconstruction?mentioning
confidence: 99%
“…Nevertheless, the rate of breast reconstruction has remained relatively low (<30%) in North America (33,34) compared with countries such as France (>80%) (35). Factors that are significantly associated with a lower rate of reconstruction among breast cancer patients include African American race or other minority races (versus Caucasian), nonmetropolitan (versus metropolitan) dwelling, receipt of radiation therapy, older age, married (versus never married or widowed) and unilateral mastectomy (versus prophylactic mastectomy of contralateral breast) (36)(37)(38).…”
Section: Who Is a Candidate For Postmastectomy Breast Reconstruction?mentioning
confidence: 99%
“…Le taux de reconstruction mammaire immédiate (RMI) est en augmentation régulière dans la plupart des pays développés [1][2][3][4], en raison de la preuve de son bénéfice sur le bien-être des patientes opérées par mastectomie pour cancer du sein et de son innocuité carcinologique [5,6]. Parmi les techniques de reconstruction, le lambeau de grand dorsal sans prothèse (LGDSP) est une technique fiable qui donne d'excellents résultats en reconstruction mammaire.…”
Section: Introductionunclassified